Assistive Technology Advancements: Revolutionising Support for Individuals with Specific Learning Disabilities - Bibi C.B; V. Mrunalini (International Journal of Trends in Humanities, 2026)
Assistive Technology (AT) has become an offer to revolutionise the provision of people with specific Learning Disabilities (SLD), making the learning process more inclusive and equal. In this paper, the current developments in AT will be discussed that cater to fundamental learning issues in reading, writing and mathematics. Text-to-speech and speech-to-text innovations, mind-mapping tools, and others are important innovations that improve reading comprehension and written expression, as well as strength organisation, memory and generate ideas, thus contributing to the improvement of literacy. Also, problem-solving and numerical comprehension can be accomplished with the help of specialised software in mathematics which is interactive and adaptive. Artificial Intelligence (AI) also enhances the personalisation of learning by examining the needs of the individual, instructional pacing, and real-time feedback, which encourages independent and self-directed learning. This paper notes the increased presence of AT in minimising learning obstacles, enhancing accessibility, and supporting inclusive education. It concludes that Assistive Technology, backed by the innovation of AI is becoming an inseparable part of contemporary educational systems, and it can bring people with SLD to the full of their potential and enable them to engage in academic and social life in a meaningful way.
Keywords: Assistive Technology Advancements; Ethical Concerns; artificial intelligence; specific learning disabilities